Internalisasi Nilai-Nilai Pendidikan Islam dalam Program Pelatihan Kaderisasi Dasar SSC (Salman Spiritual Camp) di Masjid Salman ITB - Eriani Soprian Nurjanah; Aep Saepudin (UNISBA Press, 2023)
Abstract The role and function of the mosque is not only for praying, but also multifunctional, one of which is as a center for Islamic education. This has also been true since the time of the Prophet Muhammad. The background in this study is the role and function of the mosque as a center for Islamic education. Where the focus of this research is the campus mosque which is quite strategic in fostering or regenerating students to have spiritual values. The problem in this study is about the values of Islamic education contained in the SSC (Salman Spiritual Camp) regeneration program at the Salman ITB campus mosque, the strategies used in its internalization, as well as the supporting and inhibiting factors in its implementation. In this study, the researcher used a qualitative method with a case study method. Data collection techniques through interviews and documentation studies. The data analysis technique includes the stages of data reduction, data presentation, triangulation, and conclusions. Based on the results of the study, the values of Islamic education contained in the SSC program include the values of faith, moral values, and worship values. The strategies used in its internalization include exemplary, habituation, ibrah and proverbs, giving advice, giving promises and threats, and discipline. The supporting factors are the number of participants who register and the Salman Charity House which is a source of funds for the activity. Meanwhile, the inhibiting factor is the first because the SSC activity is open to national students, it is quite difficult to flexibility in the time of program activities that adjusts to the ITB schedule. Secondly, due to the COVID-19 pandemic, the implementation of the SSC which was originally offline and carried out for two days and one night, had to change to online which took a relatively longer time, namely one week. Keywords: Value, Islamic Education, Regeneration. Abstrak Peran dan fungsi masjid tidak hanya untuk beribadah salat saja, melainkan multifungsi, salah satunya adalah sebagai pusat Pendidikan Islam. Hal tersebut juga sudah berlaku sejak zaman Rasulullah Saw. Latar belakang dalam penelitian ini adalah peran dan fungsi masjid sebagai pusat Pendidikan Islam. Dimana yang menjadi fokus penelitian ini yaitu masjid kampus yang cukup strategis dalam pembinaan ataupun pengkaderan mahasiswa untuk memiliki nilai spiritual. Masalah dalam penelitian ini adalah tentang nilai-nilai Pendidikan Islam yang terdapat dalam program kaderisasi SSC (Salman Spiritual Camp) masjid kampus Salman ITB, strategi yang digunakan dalam internalisasinya, serta faktor pendukung dan penghambat dalam pelaksanaannya. Dalam penelitian ini, peneliti menggunakan metode kualitatif dengan metode studi kasus. Teknik pengumpulan data melalui wawancara dan studi dokumentasi. Teknik analisis datanya meliputi tahap reduksi data, penyajian data, triangulasi, dan kesimpulan. Berdasarkan hasil penelitian, nilai-nilai Pendidikan Islam yang terdapat dalam program SSC meliputi nilai akidah, nilai akhlak, dan nilai ibadah. Strategi yang digunakan dalam internalisasinya meliputi keteladanan, pembiasaan, ibrah dan amtsal, pemberian nasihat, pemberian janji dan ancaman, serta kedisiplinan. Adapun faktor pendukungnya yaitu banyaknya peserta yang mendaftarkan diri serta Rumah Amal Salman yang menjadi sumber dana dalam kegiatan. Sementara itu faktor penghambatnya adalah yang pertama karena kegiatan SSC ini terbuka bagi mahasiswa nasional, cukup sulit dalam fleksibilitas waktu kegiatan program yang menyesuaikan dengan jadwal ITB. Yang kedua, karena pandemi covid-19, pelaksanaan SSC yang semula offline dan dilaksanakan selama dua hari satu malam, harus berubah menjadi online yang waktunya relative lebih lama yaitu satu pekan.Kata Kunci: Nilai, Pendidikan Islam, Kaderisasi.